Research landscape of marginal and small farmers in India from 1975 to 2024: A bibliometric analysis - Smriti; A. K. Basantaray (Journal of Tropical Agriculture, 2025)
This paper attempted a bibliometric analysis of the literature on India’s marginal and smallfarmers from 1975 to 2024, highlighted key terms, keyword co-occurrence, trending topics, research theme evolution, and future research directions for this critical group. Nearly ninety percent of India’s agricultural households were marginal and small, playing a significant role in the country’s agricultural framework. We used 309 research studies from the SCOPUS database for this purpose.The literature’s primary keywords included climate change, food security, sustainability, farmers’ income, contract farming, productivity, conservation agriculture, crop diversification, indebtedness, livelihood, institutional credit, farm size, farm income, employment, and integrated farming systems. Co-occurrence analysis indicated that researchers highly emphasized climate change, smallholder farmers, adaptation, and climate variability. Nonetheless, areas such as food security, and marginal and small farmers had adverse effects of climate change, and climate change mitigation strategies require further investigation to substantially improve the welfare of India’s marginal & small farmers.